The effects of social media and fear of missing out on university students’ online purchase decisions while using TikTok: Evidence from Northern Vietnam - Minh, Lê Quang; Duyên, Vũ Thị Mai (Edelweiss Applied Science and Technology, 2025)
The rapid expansion of social commerce has positioned TikTok as a dominant platform influencing consumer decision-making, particularly among university students in Vietnam. With the rise of short-form videos and interactive livestream shopping, users are continuously exposed to persuasive stimuli such as instant promotions, real-time product demonstrations, and socially driven cues. These features create an environment in which psychological factors, especially Fear of Missing Out (FOMO) may strongly shape online purchasing behavior. Despite growing interest in TikTok-based commerce, empirical evidence examining how social media engagement and FOMO jointly influence purchase intention and impulsive buying among Vietnamese students remains limited. To address this gap, the present study investigates the effects of social media use and FOMO on online purchase behavior while students watch TikTok livestreams. A structured questionnaire employing five-point Likert scales was administered to 300 students in Northern Vietnam, and the dataset was analyzed using SmartPLS 3. Findings reveal that sales promotions and livestream participation significantly elevate both purchase intention and impulsive buying decisions. The study contributes to the emerging literature on social commerce by highlighting the psychological and promotional mechanisms driving student purchasing behavior within TikTok’s livestream environment.